2020
DOI: 10.1098/rstb.2019.0134
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adipocyte browning in the evolution of endothermy

Abstract: Endothermy changes the relationship between organisms and their environment fundamentally, and it is therefore of major ecological and evolutionary significance. Endothermy is characterized by non-shivering thermogenesis, that is metabolic heat production in the absence of muscular activity. In many eutherian mammals, brown adipose tissue (BAT) is an evolutionary innovation that facilitates non-shivering heat production in mitochondria by uncoupling food-derived substrate oxidation from chemical energy (ATP) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…Water loss, however, could be avoided if T b is regulated slightly above ambient, and the outward flow of heat is varied by insulation, therefore, a switch to a diurnal activity pattern in some species would have necessitated higher T b s (Crompton et al, 1978), which in turn were only made possible with the evolution of the scrotum (Lovegrove, 2019). The evolution of endothermy in mammals is an emergent property of the evolution of various characteristics that aid in either heat production (e.g., thermogenesis, UCP1) and heat dissipation (e.g., insulation, external scrotums) and happened to a different degree across the mammalian lineage (Lovegrove, 2012(Lovegrove, , 2019Seebacher, 2018;Jastroch and Seebacher, 2020). By studying the added level of variability in many thermoregulatory traits, torpor use in particular, observed in species in the tropics and subtropics can help shed further light on how endothermy evolved in mammals.…”
Section: Tropical Origins Of Heterothermy and Endothermy In Mammalsmentioning
confidence: 99%
“…Water loss, however, could be avoided if T b is regulated slightly above ambient, and the outward flow of heat is varied by insulation, therefore, a switch to a diurnal activity pattern in some species would have necessitated higher T b s (Crompton et al, 1978), which in turn were only made possible with the evolution of the scrotum (Lovegrove, 2019). The evolution of endothermy in mammals is an emergent property of the evolution of various characteristics that aid in either heat production (e.g., thermogenesis, UCP1) and heat dissipation (e.g., insulation, external scrotums) and happened to a different degree across the mammalian lineage (Lovegrove, 2012(Lovegrove, , 2019Seebacher, 2018;Jastroch and Seebacher, 2020). By studying the added level of variability in many thermoregulatory traits, torpor use in particular, observed in species in the tropics and subtropics can help shed further light on how endothermy evolved in mammals.…”
Section: Tropical Origins Of Heterothermy and Endothermy In Mammalsmentioning
confidence: 99%
“…It has been shown that various physiological factors, including exercise, diet and the immune system, can cause the browning of white adipose tissue through epigenetic mechanisms [29]. In the first contribution of this section, Jastroch & Seebacher [5] review the molecular mechanisms underlying the browning of white adipocytes, and their potential contribution to endogenous heat production in the evolution of endothermy. Bal & Periasamy [6] review another mechanism of non-shivering thermogenesis: inhibition of Ca 2+ transport, but not ATP hydrolysis, of sarco-endoplasmic reticulum calcium ATPase (SERCA) by sarcolipin, resulting in a futile pump activity that generates heat.…”
Section: Thermometabolismmentioning
confidence: 99%
“…'Vertebrate palaeophysiology' will promote a better understanding of how organism-environment interactions have evolved in terms of energy budgets, predator-prey relationships and sensitivity to environmental change. The research areas covered by this theme issue include: phospho-calcic metabolism [2], acid-base homeostasis [3,4], thermometabolism [4][5][6][7][8][9], respiratory physiology [10], skeletal growth [11], palaeopathophysiology [12,13], genome size and metabolic rate [14], and a concluding historical perspective [15]. Sometimes, the two components ( physiological mechanism and palaeobiological inference) are proposed in separate papers (for instance, three contributions devoted to mechanisms of thermogenesis mechanisms [5][6][7] and three papers dealing with the thermometabolic inferences in extinct taxa [4,8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…Endothermy has evolved many times in vertebrates, and proceeds by varied mechanisms ( Jastroch and Seebacher, 2020 ; Legendre and Davesne, 2020 ). Thermogenic adipoctyes, and the presence of brown adipose tissue depots, are unique to placental mammals.…”
Section: Discussionmentioning
confidence: 99%